Thromboprophylaxis with Low-Molecular-Weight Heparins: An Assessment of the Methodological Quality of Studies - Agnelli, Giancarlo; Prandoni, Paolo; Di Minno, Giovanni; Cimminiello, Claudio; Scaglione, Francesco; Boracchi, Patrizia; Molteni, Mauro; Polo Friz, Hernan; Di Minno, Matteo Nicola Dario; Marano, Giuseppe (Seminars in Thrombosis and Hemostasis, 2015)
Low-molecular-weight heparin (LMWH) represents the standard of care for prophylaxis of venous thromboembolism (VTE). We conducted a review of the evidence supporting the use of the different LMWHs employed in VTE prophylaxis, in different clinical settings, and analyzed its progression over time. To evaluate the standards of methodological quality of studies, we elaborated a quality assessment tool. By electronic databases, PubMed, MEDLINE, and Scopus databases, 249 articles deemed eligible for the analysis were selected. Several LMWHs did not have publications in all clinical settings. Extended duration of prophylaxis was documented only for a few LMWH. The quality score yielded statistically significant differences between the medians of the four settings (p = 0.0021) with a higher score in major orthopedic surgery (median, 16; 95% confidence interval [CI], 15–16) when compared with general surgery (median, 14; 95% CI, 13–14; p < 0.001). Median score for studies published after the year 1990 was higher than for those published earlier (p < 0.001). We conclude that the quality of the studies supporting LMWH for VTE prophylaxis in the different clinical settings is not homogeneous and inferior for studies performed before the year 1990. Clinical interchangeability of LMWHs in clinical practice remains a critical issue, and the selection of a product should be based on evidence available for each agent, and for each clinical indication derived from clinical trials.
Keywords: low-molecular-weight heparin; evidence-based practice; therapeutic equivalency; venous thromboembolism; systematic review